Genetic Diversity and Low Therapeutic Impact of Variant-Specific Markers in HIV-1 Pol Proteins - Troyano-Hernáez, Paloma; Reinosa, Roberto; Holguín, Africa (Frontiers in Microbiology, 2022)
The emergence and spread of new HIV-1 variants pose a challenge for the effectiveness of antiretrovirals (ARV) targeting Pol proteins. During viral evolution, non-synonymous mutations have fixed along the viral genome, leading to amino acid (aa) changes that can be variant-specific (V-markers). Those V-markers fixed in positions associated with drug-resistance mutations (DRM), or R-markers, can impact drug susceptibility and resistance pathways. All available HIV-1 Pol sequences from ARV-naïve subjects were downloaded from the US-Los-Alamos-HIV-Sequence-Database, selecting 59,733 protease (PR), 6,437 retrotranscriptase (RT), and 6,059 integrase (IN) complete sequences ascribed to the four HIV-1 groups and group M subtypes and circulating recombinant forms (CRF). Using a bioinformatics tool developed in our laboratory (EpiMolBio), we inferred the consensus sequences for each Pol protein and HIV-1 variant to analyze the aa conservation in Pol. We analyzed the Wu-Kabat protein variability coefficient (WK) in PR, RT, and IN group M to study the susceptibility of each site to evolutionary replacements. We identified as V-markers the variant-specific aa changes present in >75% of the sequences in variants with >5 available sequences, considering R-markers those V-markers that corresponded to DRM according to the IAS-USA2019 and Stanford-Database9.0. The mean aa conservation of HIV-1 and group M consensus was 82.60%/93.11% in PR, 88.81%/94.07% in RT, and 90.98%/96.02% in IN. The median group M WK was 10 in PR, 4 in RT, and 5 in IN. The residues involved in binding or catalytic sites showed a variability <0.5%. We identified 106 V-markers: 31 in PR, 28 in RT, and 47 in IN, present in 11, 12, and 13 variants, respectively. Among them, 8 (7.5%) were R-markers, present in 5 variants, being minor DRM with little potential effect in ARV susceptibility. We present a thorough analysis of Pol variability among all HIV-1 variants circulating to date. The relatively high aa conservation observed in Pol proteins across HIV-1 variants highlights their critical role in the viral cycle. However, further studies are needed to understand the V-markers´ impact on the Pol proteins structure, viral cycle, or treatment strategies, and periodic variability surveillance studies are also required to understand PR, RT, and IN evolution.